2017
DOI: 10.1097/md.0000000000007955
|View full text |Cite
|
Sign up to set email alerts
|

Classification and possible bacterial infection in outpatients with eczema and dermatitis in China

Abstract: Little is known about the classification and bacterial infection in outpatients with eczema and dermatitis in China.To investigate the prevalence of eczema and dermatitis in outpatients of dermatology clinics in China, examine classification and proportion of common types of dermatitis and the possible bacterial infection, and analyze the possible related factors.Outpatients with eczema or dermatitis from 39 tertiary hospitals of 15 provinces in mainland China from July 1 to September 30, 2014, were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…A previous study from our institute has demonstrated that the clinical diagnosis was highly correlated with the laboratory bacterial culture results; S. aureus was isolated in 92.9% of eczema patients who were diagnosed with very likely bacterial infection [16]. No laboratory test was performed to make the diagnosis [17,18].…”
Section: Data Collection and Diagnosismentioning
confidence: 99%
“…A previous study from our institute has demonstrated that the clinical diagnosis was highly correlated with the laboratory bacterial culture results; S. aureus was isolated in 92.9% of eczema patients who were diagnosed with very likely bacterial infection [16]. No laboratory test was performed to make the diagnosis [17,18].…”
Section: Data Collection and Diagnosismentioning
confidence: 99%
“…In 2014, a crosssectional study in China reported that 52.3% of AD patients of all ages had secondary bacterial infection. 6 This study analyzed the relationship between risk factors and the incidence of secondary bacterial infections in AD. The risk factors examined were individual/familial history of atopy, dry skin, and involvement of the flexor area.…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, it can lead to several systemic infections such as osteomyelitis, septicemia, and endocarditis. 5,6,7 The risk factors for secondary bacterial infection in AD have not been determined. Research in China reported the risk factors associated with the incidence of secondary bacterial infection in AD patients: history of allergies, history of AD in infancy, and involvement of the flexor area.…”
Section: Introductionmentioning
confidence: 99%
“…Irritation of hands can even lead to the triggering of other dermatoses [5]. Due to the appearance of fissures and irritated eczematous areas, the threat of secondary bacterial infection becomes a concern [6].…”
Section: Sirmentioning
confidence: 99%